Analisis Hukum Kebijakan Pemerintah dalam Memajukan Kemandirian Lokal: Perspektif Ketahanan Pangan Nasional - Juwenie Juwenie; Muh Fadli Faisal R; RR Eko Widy Astuty Sumanto; Haeruddin Haeruddin; Sri Handayani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
National food security is one of the crucial issues or problem that is the focus of government attention in order to ensure the availability, access, and quality of food for the entire community. Government policies that support local independence are believed to have an important role in achieving sustainable food security. This study aims to analyze government policies from a legal perspective in advancing local independence and their implications for national food security. The methodology used in this study is normative legal analysis with a descriptive approach. The data used comes from primary sources such as laws and regulations and related policies, as well as secondary sources in the form of literature and other supporting documents. The analysis is carried out to identify policies that have been implemented, evaluate their effectiveness, and the legal implications that arise. The results of the study show that there are a number of policies that have been implemented by the government to advance local independence, but there are still various challenges in their implementation. Several policies that are effective at the local level have not been fully integrated with national policies, which causes a lack of harmony in achieving food security. In addition, this study found that the legal aspects of the policy still need improvement to support the sustainability of local independence in the long term. The conclusion of this study emphasizes the importance of strengthening a more integrated legal and policy framework that focuses on local empowerment. Recommendations are given to policy makers to improve existing regulations, improve coordination between institutions, and encourage local community participation in efforts to achieve sustainable national food security.